Validação de método e determinação de Ptaquilosídeo e Pterosina B por cromatografia líquida de alta eficiência em samambaias e no leite de vacas - Debora da Silva Freitas Ribeiro (2018)
The species Pteridium spp. is a poisonous plant known as bracken fern. The existing species in Brazil are: P. arachnoideum and P. caudatum. The fern has already been recorded in practically all Brazilian states. As for its occurrence, it is present in mountainous regions, from the south of Bahia to Rio Grande do Sul states, but is also invasive in areas of the states of Amazonas, Acre, Mato Grosso and Pernambuco. It is found in cold regions of high rainfall, acid soils, sandy and well drained. P. arachnoideum has two toxic principles: thiaminase, responsible for monogastric intoxication, and ptaquiloside (Pta), the carcinogenic substance responsible for intoxication in ruminants. Production animals consume the fern, especially its younger parts, even though it is not palatable. The effects of the ingestion are several, depending on the animal species and the dose ingested. Five different clinical syndromes are described in the literature: thiamine deficiency, progressive retinal degeneration, acute hemorrhagic syndrome (hemorrhagic diathesis), bovine enzootic hematuria (BEH) and upper digestive tract carcinomas. The currently available techniques for determination of Pta promote its conversion into pterosin B (PtB), but this has limited commercial availability. The aim of the present study was to develop a methodology for obtaining pterosin B (PtB) and for determining the amount of the ptaquiloside (Pta) carcinogen in plants and milk by high performance liquid chromatography (HPLC). Pta and PtB were measured in ferns Pteridium arachnoideum, collected in the states of Minas Gerais and Rio Grande do Sul, and in Dicranoptris flexuosa, Gleichenella pectinata and Sticherus lanuginosus collected in the state of Minas Gerais. In addition, samples of the ferns Pteris deflexa and Pteris plumula were sampled from Argentinian farms with BEH cases, but free of any Pteridium species. A total of 47 samples of mature leaves and 23 shoots samples were used. Blank milk samples were used for the development and evaluation of the analytical technique. For the application of the validated technique, 60 samples of raw tank milk from from several farms in Minas Gerais (MG) state, and 20 samples of raw milk from small properties from Ouro Branco city, MG, and 5 samples from Esmeraldas city, MG, both with cases of HEB and presence of P. arachnoideum in the rangeland. The concentration of Pta in leaf samples of P. arachnoideum ranged from 2.486±0.439 to 2.753±0.844 mg/g and PtB ranged from 0.684±0.152 to 0.885±0.197 mg/g, in P. arachnoideum sprouts Pta values ranged from 12.472±5.620 to 18.809±2.338 mg/g and PtB ranged from 4.026±0.982 to 10.424±0.233 mg/g. The values found in P. deflexa and P. plumula for Pta ranged from 2.424 to 3.235 mg/g and for PtB ranged from 0.727 to 1.543 mg/g. In addition, S. lanuginosus showed Pta levels of 2.466±0.173 mg/g and PtB levels of 1.572±0.166 mg/g, and D. flexuosa had Pta levels of 0.892-0.215 mg/g and PtB 0.466-0.083 mg/g. In G. pectinata, these toxic compounds were not detected until the present moment. Thus, S. lanuginosus and D. flexuosa were identified for the first time as producers of Pta and PtB, potentially toxic to ruminants. Regarding the methodologies used for the clean-up of the milk samples, two methods were efficient in cleaning the matrix and in the recovery of the standard after fortification tests. However, no milk samples were found positive for Pta and PtB.